A child from the village - Quṭb, Sayyid, 1906-1966 (Middle East literature in translation., 2016)
"Although the Egyptian writer Sayyid Qutb is not a household name in the United States, he is well known throughout the Islamic World as a seminal thinker in the Islamist movement, influential as far away as Pakistan and Malaysia. A member of the Islamic Brotherhood, he was jailed by Gamal Abdul Nasser's government as early as 1954. He became one of the most uncompromising voices of the movement we now call Islamism and is best known perhaps for his book, Ma'lam fi al-tariq, after publication of which he was accused of conspiring against Egyptian president Nasser and arrested. He was executed in 1966."